Implementation of social security chronic disease management program in yogyakarta - Rochana Ruliyandari; Bambang Purwanto; AA Subiyanto; Suwarto Suwarto (Universitas 'Aisyiyah Yogyakarta, 2021)
Elderly is a global concern since the number of elderly populations is increasing, which also become one of the concerns of the national health insurance (JKN). Health insurance for the elderly has a package of benefits according to physical conditions and degenerative diseases. Since the elderly is susceptible to disease, Indonesia has Healthcare and Social Security Chronic Disease Management Program, National Health Insurance known as Badan Penyelenggara Jaminan Sosial Program Pengelolaan Penyakit Kronis (BPJS Prolanis) to guarantee the health of elderly. This study aims to obtain an overview of the implementation of BPJS Prolanis in the community which located in Yogyakarta in order to give the feedback for this program. This research using qualitative method, with phenomenological research approach, which conducted in Yogyakarta during 2020. The result showed that most of the elderly, which is 221 (77.5%) elderly already have the health insurance, but only 38.9% who has BPJS Prolanis. Besides, there are more than 50% of the elderly have disease that often complained of. Hence, this study proposed suggestions for BPJS Prolanis, such as giving a continues education for the elderly through public health center. Besides, public health center can hold a promotive and preventive activities for the elderly to increase the awareness of the elderly on having the BPJS Prolanis.